Towards collaborative applications using web services - Coppo, Ricardo (2006)
Web services are becoming popular as a system integration solution for distributed applications. They allow for publishing, finding and binding of distributed software components over a Wide Area Network like the Internet and are platform and operating system independent. In a traditional scenario, ontologies are defined and published by a consortium or enterprise group for each application discourse. These specifications can later be implemented by many web service providers.